Cerebellar transcranial direct current stimulation improves adaptive postural control. Issue 1 (January 2018) - Poortvliet, Peter; Hsieh, Billie; Cresswell, Andrew; Au, Jacky; Meinzer, Marcus
Highlights: Rehabilitation interventions for recovery of postural control are effective, but time consuming and costly. Offline cerebellar tDCS can improve postural steadiness in a healthy population. These findings may have implications for optimizing rehabilitation interventions in clinical settings. Abstract: Objective: Rehabilitation interventions contribute to recovery of impaired postural control, but it remains a priority to optimize their effectiveness. A promising strategy may involve transcranial direct current stimulation (tDCS) of brain areas involved in fine-tuning of motor adaptation. This study explored the effects of cerebellar tDCS (ctDCS) on postural recovery from disturbance by Achilles tendon vibration. Methods: Twenty-eight healthy volunteers participated in this sham-ctDCS controlled study. Standing blindfolded on a force platform, four trials were completed: 60 s quiet standing followed by 20 min active (anodal-tDCS, 1 mA, 20 min, N = 14) or sham-ctDCS (40 s, N = 14) tDCS; three quiet standing trials with 15 s of Achilles tendon vibration and 25 s of postural recovery. Postural steadiness was quantified as displacement, standard deviation and path derived from the center of pressure (COP). Results: Baseline demographics and quiet standing postural steadiness, and backwards displacement during vibration were comparable between groups. However, active-tDCS significantly improved postural steadiness during vibration and reduced forward displacement and variability in COP derivatives during recovery. Conclusions: We demonstrate that ctDCS results in short-term improvement of postural adaptation in healthy individuals. Significance: Future studies need to investigate if multisession ctDCS combined with training or rehabilitation interventions can induce prolonged improvement of postural balance.